Penggunaan Teknologi Artificial Intelligence Dalam Penulisan Buku - Muhtajuddin Danny; Elkin Rilvani; Edora; Iwan Mulyana (VINICHO MEDIA PUBLISINDO, 2024)
Training on the use of Artificial Intelligence (AI) technology in book writing is a response to the rapid development of information and communication technology which has influenced various aspects of life, including the publishing and writing industry. AI technology has developed rapidly and shown its potential in various fields, including data analysis, natural language processing (NLP), and machine learning (Machine Learning). AI algorithms can generate text, analyze writing style, and provide relevant recommendations for writers. AI can help writers in various stages of the writing process, from brainstorming ideas, creating initial drafts, to editing. Tools like GPT-4 can generate paragraphs or chapters based on specific instructions, which helps speed up the writing process and overcome creative barriers. The use of AI can improve the quality of writing by providing suggestions for editing and improvement. AI can also ensure consistency in writing style and use of terminology, which is especially important in writing technical books or series. In the digital era, speed and quality of content production are key factors in competition. Authors and publishers who are able to utilize AI technology can have a competitive advantage by producing books faster and with better quality.